Exploring the therapeutic and anti-tumor properties of morusin: a review of recent advances - Hafeez, Amna; Khan, Zeeshan; Armaghan, Muhammad; Khan, Khushbukhat; Sönmez Gürer, Eda; Abdull Razis, Ahmad Faizal; Modu, Babagana; Almarhoon, Zainab M.; Setzer, William N.; Sharifi-Rad, Javad (Frontiers Media S.A., 2023)
Morusin is a natural product that has been isolated from the bark of Morus alba, a species of mulberry tree. It belongs to the flavonoid family of chemicals, which is abundantly present in the plant world and is recognized for its wide range of biological activities. Morusin has a number of biological characteristics, including anti-inflammatory, anti-microbial, neuro-protective, and antioxidant capabilities. Morusin has exhibited anti-tumor properties in many different forms of cancer, including breast, prostate, gastric, hepatocarcinoma, glioblastoma, and pancreatic cancer. Potential of morusin as an alternative treatment method for resistant malignancies needs to be explored in animal models in order to move toward clinical trials. In the recent years several novel findings regarding the therapeutic potential of morusin have been made. This aim of this review is to provide an overview of the present understanding of morusin’s beneficial effects on human health as well as provide a comprehensive and up-to-date discussion of morusin’s anti-cancer properties with a special focus on in vitro and in vivo studies. This review will aid future research on the creation of polyphenolic medicines in the prenylflavone family, for the management and treatment of cancers.